FDI spillovers in transitive economies integrating into the EU in case of the Baltic countries - Shkabarin, Georgiy (Economics of the 21st Century, 2015)
The paper deals with the idea of spillovers (or indirect effects) from foreign direct investment increasing the firm productivity in transitive economies under the circumstances of economic integration. The Baltic countries are the best example of such a kind of states. The indirect effects for the productivity are examined both at a country and at a firm level with the use of a proved estimation model in order to probe for the existence, sign and magnitude of different types of spillovers. The paper includes a brief historical analysis of the previous works and the history of elaboration of an estimation model for spillovers. The analysis of FDI inflows in Estonia, Latvia and Lithuania with diagrams is included to visualize the change in the attitude of foreign investors to these countries during the post-soviet period and after their accession to the EU
Ekonomia XXI Wieku = Economics of the 21st Century, 2015, Nr 4 (8), s. 20-29
Keywords: FDI; spillovers; productivity; Latvia; Lithuania; Estonia; BIZ; spillowery; efekty pośrednie; wydajność; Łotwa; Litwa